Structural, magnetic and optical properties of diluted magnetic semiconductor (DMS) phase of Ni modified CuO nanoparticles - Kumar, Arvind; Kumar, Manish; Chandra Sati, Prakash; Srivastava, Manish Kumar; Ghosh, Surajit; Kumar, Shiv (Current applied physics, 2021)
Control on the size of copper oxide (CuO) in the nano range is a highly motivating approach to study its multifunctional nature. The present investigation reports a sol-gel derived Ni doped CuO nanoparticles (Cu1-xNixO). Rietveld refinement of the XRD spectra confirms the formation of single monoclinic phase of Cu1-xNixO nanoparticles having crystallite size within the range of 19–21 nm. Raman spectra show the presence of characteristics Raman active modes and vibrational bands in the Cu1-xNixO samples that corroborate the monoclinic phase of the samples as revealed by refinement of XRD data. The estimated band gap of pure CuO is found to be ∼1.43 eV, which decreases with the increase of dopant concentration into CuO matrix. This result is in line with estimated crystallite size. Magnetization curves confirm the weak ferromagnetic nature of Cu1-xNixO nanoparticles which reveal the DMS phase. This weak magnetic nature may be induced in the samples due to the exchange interaction between the localized magnetic d-spins of Ni ions and carriers (holes or electrons) from the valence band of pristine CuO lattice. Replacement of Cu+2 by Ni+2 ions into the host CuO lattice induces the magnetization. The quantified value of squareness ratio (S < 0.5) confirms the inter-grain magnetic interactions in the Cu1-xNixO nanoparticles which is also the reason of weak induced magnetization. [Display omitted] •Cu1-xNixO nanoparticles were successfully synthesized via chemical sol-gel route.•Structural study shows the formation of single phase nanoparticles (19–21 nm).•Optical band gap of CuO (∼1.43 eV) found to red shifted on doping with Ni ion.•M-H loops show the weak ferromagnetism for Cu1-xNixO nanoparticles.•Present study reveals the DMS phase at room temperature.